CONSTRUCTION OF SONDONG IN BANTAN DISTRICT, BENGKALIS REGENCY - Renny Afri Artika; Arthur Brown; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in April 2018, located in Bantan District, Bengkalis Regency. This study aims to find out about the material and construction of sondong, as well as how to operate in the District of Bantan.The method used in this research is survey. Sondong in Bantan District uses human power in its operation, its different from sondong in other areas that use ships when is operated, this makes researchers interested in knowing how sondong construction in Bantan District. Sondong net construction in Bantan District does not have a significant difference. construction on the buoy, ballast, upper ris, lower ris lines is basically the same in every village. Keywords: Construction, Sondong, District of Bantan.